Criminal Liability of Bounced Check Fraud Perpetrators in Criminal Law Perspective: A Case Study of Decision Number 1698/Pid.B/2022/PN Sby - Firman Syah Permadi; M. Taufik; Sri Sukmana Damayanti (International Journal of Law and Society, 2026)
This research aims to analyze the criminal liability of perpetrators of fraud through bounced checks and the legal protection provided to victims. The study focuses on Decision Number 1698/Pid.B/2022/PN Sby, in which the defendant was found guilty of fraud under Article 378 of the Indonesian Criminal Code (KUHP). Using a normative juridical approach through literature study with statutory and conceptual approaches, the findings demonstrate that the panel of judges correctly applied the elements of fraud, including malicious intent (mens rea), the use of deception or a series of lies, and actual loss suffered by the victim. The judge's legal considerations have reflected the principles of legality, justice, and legal certainty in criminal law. Legal protection for victims can be pursued through both criminal and civil legal remedies, where victims may report to police for criminal prosecution under Article 378 KUHP and claim compensation through civil breach of contract lawsuits. Law enforcement against perpetrators is carried out through repressive and preventive criminal sanctions. This decision confirms that bounced check fraud is not merely a civil breach of contract but can be classified as a criminal offense when accompanied by malicious intent to deceive others.